Orbital debris and the market for satellites - Bongers-Chicano, Aneli María; Torres-Chacón, José Luis (Elsevier, 2023)
This paper studies the economic consequences of orbital debris for commercial outer-space activities. Spacecraft launches and other outer-space human activities produce pollution (i.e., orbital debris), which represent a hazardous negative externality increasing the risk of collision and the destruction of satellites. We regard outer space as a global common resource, where firms operating satellites maximize profits and do not internalize the social cost of orbital pollution. We develop a dynamic investment model for satellites and simulate the calibrated model to estimate how debris affects the optimal quantity of satellites and launches, and the number of satellites destroyed by collisions. We find that the optimal quantity of satellites is a negative function of the amount of debris. The paper derives a simple expression for the maximum number of satellites to prevent the Kessler syndrome. For the baseline calibration of the model, the estimated threshold for the maximum number of satellites in orbit is about 72,000. The model is simulated to study the effects of a decline in the launch cost and the increasing number of satellites per launch.
Keywords: Basura espacial-Aspectos económicos; Satélites artificiales-Aspectos económicos; Outer space; Satellites; Launches; Debris; Risk of collision; Kessler syndrome